Role of buccal corridor in smile esthetics and its correlation with underlying skeletal and dental structures - Tripti Tikku; Rohit Khanna; R P Maurya; Nabeel Ahmad (Wolters Kluwer Medknow Publications, 2012)
Purpose: This study was designed to evaluate the buccal corridor in smile esthetics and to correlate it with underlying hard tissues. Materials and Methods: Posed smiling frontal photographs, digital posterior-anterior (PA) cephalograms, and study models of 25 males and 25 females in age range of 18-25 years were taken. Photographs were evaluated for smile esthetics by eight orthodontists, eight plastic surgeons, eight beauticians and eight lay people to group them into three groups with least attractive, average and attractive smile and buccal corridor width was measured. Digital PA cephalograms were transferred on Nemo-tech software for frontal facial analysis. Intercanine and intermolar widths were measured on upper study model with the help of a digital calliper. Results: The buccal corridor width was least in attractive smile group and maximum in least attractive smile group. The buccal corridor width had a negligible correlation with hard tissues and a mild to moderate inverse correlation with intercanine and intermolar widths within the groups. Conclusion: As the amount of buccal corridor display was increased, smiling images were scored less attractive by the evaluators. The buccal corridor is not influenced by underlying skeletal hard tissues but have mild to moderate inverse correlation with the intercanine and intermolar width.